KEKERASAN DALAM KONFLIK AGRARIA: KEGAGALAN NEGARA DALAM MENCIPTAKAN KEADILAN DI BIDANG PERTANAHAN - Astuti, Puji (Faculty of Social and Political Sciences Diponegoro University, 2011)
Abstract:Violence became a common phenomenon on the case of agrarian conflict in Indonesia. Those conflict involving three main actors such as peasant, business and government. Land policy on New Order Regim that influenced by global capitalistic was take over land from the peasant by repressive ways. Many peasant in all around of Indonesia lost their land as their life resources. For many years they struggle to defend their land, but Suharto's government supported by police and military force attack them with violence action, including fired with rifle. To avoid more victim, open struggle of peasant must be stopped. But their struggle was never ending. When Soeharto's Regim toppled from his position, peasant got a good moment for continuing their struggle and reclaiming was choose as a new strategy. Reclaiming also followed by violence action that they believed would be effective to support their struggle. Violence action of course not being the best way and government should find solution by intervention policy. The most important of intervention policy was to build equity of land structure in Indonesia. It is proper that landreform elected as the best way to bring about of constitutionl obligation, mainly to take care welfare for all citizens. Keyword : Violence, Agrarian Conflict, Landreformpermalink: http://ejournal.undip.ac.id/index.php/forum/article/view/3158